2009
DOI: 10.1002/jcop.20346
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal mediators linking acculturation stressors to subsequent internalizing symptoms and self‐esteem in latino adolescents

Abstract: The specific aim of this study was to examine pathways leading to internalizing symptoms and self-esteem in Latino adolescents. Adolescent feelings of interpersonal humiliation, family conflict and commitment, and friendships with peers were investigated as potential mediators linking acculturation stress to subsequent adolescent self-esteem and internalizing symptoms. Path analyses on data from a sample of 288 Latino adolescents (average age 15 years; 66% foreign-born) showed that acculturation conflicts and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 53 publications
2
32
0
Order By: Relevance
“…The limited research on gender and familial cultural values has found that females tend to report fewer freedoms and more obligations (Comas-Diaz 1987;Raffaelli and Ontai 2004). While familial cultural values have been associated with resilient outcomes in Latino adolescents (e.g., higher grades, fewer depressive symptoms, and greater school belonging) (Ayón et al 2010;Esparza and Sánchez 2008;Gamble and Modry-Mandell 2008;Germán et al 2009;Smokowski et al 2009;Stein et al 2013), none of these past studies specifically tested whether gender moderated their results, and it is still unclear whether familial cultural values differentially predict psychosocial outcomes relative to gender. Therefore, the goal of the present study is to bridge the gap between these two bodies of research by exploring how the relationship between familial cultural values and psychological and school outcomes operates in female versus male Latino adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…The limited research on gender and familial cultural values has found that females tend to report fewer freedoms and more obligations (Comas-Diaz 1987;Raffaelli and Ontai 2004). While familial cultural values have been associated with resilient outcomes in Latino adolescents (e.g., higher grades, fewer depressive symptoms, and greater school belonging) (Ayón et al 2010;Esparza and Sánchez 2008;Gamble and Modry-Mandell 2008;Germán et al 2009;Smokowski et al 2009;Stein et al 2013), none of these past studies specifically tested whether gender moderated their results, and it is still unclear whether familial cultural values differentially predict psychosocial outcomes relative to gender. Therefore, the goal of the present study is to bridge the gap between these two bodies of research by exploring how the relationship between familial cultural values and psychological and school outcomes operates in female versus male Latino adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Attitudinal familism measures an individual's thoughts and feelings on the three different aspects of familism: (a) supportive familism signifies the level to which the individual feels supported by his or her family and the degree of closeness in their family; (b) obligatory familism is the extent to which an individual believes the family has a responsibility to provide support (economic, social, or emotional) to other family members; and (c) referent familism is the extent to which one maintains behaviors that are consistent with the family values and expectations (Sabogal et al, 1987; Marsiglia et al, 2009). It is frequently specified that involvement in Latino culture is critical for high familism attitudes and that greater acculturation to American culture and more time spent in the United States is linked to lower levels of familism (Smokowski et al, 2009). Studies included in this meta-analysis measured attitudinal familism, through a series of questions or familistic statements based on a Likert scale.…”
Section: Familismmentioning
confidence: 99%
“…Both evidences for and against the Hispanic Paradox have placed a demand for research, to understand the factors associated with the health outcomes of Latinos. Hispanic cultural values have become an area of interest due to the suggested protective factor that they may serve (Smokowski et al, 2009; Calzada et al, 2012). One of the most studied Hispanic core cultural values is familismo or familism in which a higher emphasis is placed on the family unit in terms of respect, support, obligation, and reference (Calzada et al, 2012).…”
mentioning
confidence: 99%
“…Greater heritage culture orientation may facilitate closer and more positive family relationships, thus leading to better mental health (Jasinskija-Lahti & Liebkind, 2001;Oppedal et al, 2004;Sam & Oppedal, 2002;Smokowski, Bacallao, & Buchanan, 2009). Thus, orientations to majority and heritage cultures have been linked to various aspects of positive youth development in both school and family contexts.…”
Section: Associations With Positive Youth Developmentmentioning
confidence: 99%